Analysis of Learning Communication Using the Verbal Interaction Category Systems (VICS) Model for Prospective Vocational Teachers - Iriani, Tuti; Saleh, Rosmawita; Febriyanti, Ine (Universitas Veteran Bangun Nusantara, 2025)
This research is motivated by the lack of ability of prospective teachers in communicating with students which causes the learning process to be less effective. The purpose of this study is to analyze learning communication using the VICS (Verbal Interaction Category Systems) model for prospective vocational teachers in the Teaching Skills Practice (PKM). This research method uses a qualitative descriptive approach with case study analysis. The sample is students who are taking part in the Teaching Skills Practice (PKM) at SMK Teknik Bangunan as many as 3 people. Data collection uses interaction observation instruments, interviews and documentation. The results of the study showed that the average frequency of areas A, B, D, E, D, H, I was very high at 46.65% which stated that prospective teachers still dominate during learning activities compared to students, the frequency of areas C, G, J, K, L, M, P, Q, R was 30.37% which stated that there was already feedback interaction between prospective teachers and students, and the frequency of areas N, O, S, T was only 22.98% which stated that student activities were still too passive compared to teachers during the learning process in class. Thus, it can be concluded that learning communication carried out in teaching skills practice is dominated by the teacher.